2003
DOI: 10.2355/isijinternational.43.71
|View full text |Cite
|
Sign up to set email alerts
|

SIMS/XPS Studies of Surface Layer Formed in Fe-Si-Mn Alloys by Oxygen Penetration.

Abstract: Secondary ion mass spectrometry (SIMS) and X-ray photoelectron spectroscopy (XPS) have been used for analyzing surface layers formed in Fe-Si-Mn alloys containing 1, 2, 3 and 4.5 mass% silicon, which were annealed in hydrogen and argon gases with a low partial pressure of oxygen. SIMS depth profiles showed that silicon in these alloys is reacted with oxygen penetrating into the bulk to form silicon oxides, and the characteristic distribution of silicon oxides is obtained in the surface layer, depending on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…The thickness of the oxide thin films increased with aluminum content. The refractivity values were consistent with that of aluminum oxides [17,18], although the refractivity of Sample A was lower than those of Samples B and C. This indicated that the chemical composition or density of the oxide film of Sample A deviated from that of aluminum oxide, which may arise from vanadium enrichment between the oxide film and substrate. Figure 8 shows the thickness values of aluminum oxide films on the FeCo-V alloys measured using ellipsometry versus aluminum content.…”
Section: Ellipsometry and CLsupporting
confidence: 58%
“…The thickness of the oxide thin films increased with aluminum content. The refractivity values were consistent with that of aluminum oxides [17,18], although the refractivity of Sample A was lower than those of Samples B and C. This indicated that the chemical composition or density of the oxide film of Sample A deviated from that of aluminum oxide, which may arise from vanadium enrichment between the oxide film and substrate. Figure 8 shows the thickness values of aluminum oxide films on the FeCo-V alloys measured using ellipsometry versus aluminum content.…”
Section: Ellipsometry and CLsupporting
confidence: 58%
“…Such correlations of oxygen and a reactive element in depth profiles were also observed in Fe-Si alloys. [11,12] Formation of aluminum oxide on the alloy surface A reactive element in a surface layer is distributed by the selective oxidation of the element, which is related to the mobility of the element in the alloy matrix. [8,11] Therefore, the kinetics of the formation of Al 2 O 3 layers on the sample surfaces should be discussed on the basis of the mobility of aluminum in the ironbased alloys.…”
Section: Sims Depth Profilesmentioning
confidence: 99%
“…Some samples after annealing in air were further annealed in Ar‐10% H 2 at 873 K for 3600 s (Condition (d)). When the alloys are annealed under the Ar‐10% H 2 gas atmosphere in which the partial pressure of oxygen is approximately 10 −13 Pa, it is considered that gallium is oxidized, whereas iron is not oxidized in the alloys, and hydrogen has little effect on surface reaction on iron‐based alloys 11 …”
Section: Methodsmentioning
confidence: 99%
“…is considered that gallium is oxidized, whereas iron is not oxidized in the alloys, and hydrogen has little effect on surface reaction on iron-based alloys. 11…”
Section: Introductionmentioning
confidence: 99%